Attitudes and perceptions towards developing a health educational video to enhance optimal uptake of malaria preventive therapy among pregnant women in Uganda: a qualitative study involving pregnant women, health workers, and Ministry of health officials - Rita Nakalega; Ruth Nabisere-Arinaitwe; Nelson Mukiza; Cynthia Ndikuno Kuteesa; Denis Mawanda; Paul Natureeba; Ronnie Kasirye; Clemensia Nakabiito; Jane Nabakooza; Emmie Mulumba; Josephine Nabukeera; Joseph Ggita; et al. (BMC, 2024)
Abstract Background Malaria in pregnancy remains a major global public health problem. Intermittent prophylaxis treatment of malaria in pregnancy with Sulphadoxine-pyrimethamine and co-trimoxazole is efficacious for prevention of malaria in pregnancy HIV negative and positive women, respectively. However, uptake of the recommended doses of therapies has remained suboptimal in Uganda, majorly due to inadequate knowledge among pregnant women. Therefore, this study aimed to explore attitudes and perceptions towards developing an educational video for malaria preventive therapy. Methods We conducted an exploratory study with qualitative methods among pregnant women attending antenatal care at Kisenyi Health Center IV (KHCIV), health workers from KHCIV, and officials from the Ministry of Health. The study was conducted at KHCIV from October 2022 to March 2023. Focus group discussions (FGD) were conducted among purposively selected pregnant women and key informant interviews (KII) among health workers and Ministry of Health officials. Data were analyzed using inductive and deductive thematic methods in atlas ti.8. Results A total of five FGDs comprising of 7-10 pregnant women were conducted; and KIIs were conducted among four mid-wives, two obstetricians, and two Ministry of Health officials. Generally, all respondents mentioned a need for interventions to improve malaria preventive knowledge among pregnant women; were positive about developing an educative video for malaria preventive therapy in pregnancy; and suggested a short, concise, and edutaining video focusing both the benefits of taking and risks of not taking malaria preventive therapy. They proposed that women may be encouraged to view the video as soon as they conceive and throughout the pregnancy. It also was suggested that the video may be viewed on television sets in maternal and reproductive health clinics and homes, and on smart phones. Conclusion Pregnant women, health workers, and Ministry of Health officials were positive about the development of a short edutaining video on malaria preventive therapy that focuses on both benefits of taking and risks of not taking the malaria preventive therapy in pregnancy. This information guided the video development and therefore, in the development of health educative videos, client and stakeholder inputs may always be solicited.